2019
DOI: 10.1007/s00167-019-05683-0
|View full text |Cite|
|
Sign up to set email alerts
|

Arthroscopic correction of femoroacetabular impingement improves athletic performance in male athletes

Abstract: Purpose To measure the changes in athletic performance in athletes treated arthroscopically for femoroacetabular impingement and compare results to a matched controlled athletic cohort, over a 1‐year period. Methods Male athletes scheduled for arthroscopic correction of symptomatic FAI were recruited and tested (pre‐operatively and 1‐year postsurgery) for measures of athletic performance which included acceleration (10‐m sprint), change of direction speed (CODS), squatting depth, and reactive strength index (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…12,22,32 Additionally, many cohort studies suggest that hip arthroscopy for FAIS is associated with large and clinically relevant improvements in pain and function pre-to postoperatively. 17,23,24,30,39 Many patients, however, still present with persistent hip and groin pain and functional limitations after surgery, 17,18,21,39 indicating that discrepancies may exist between "getting better" and "feeling good." 25 To better understand if patients consider their current state of health (eg, pain and function) to be at an acceptable level after hip arthroscopy for FAIS, the Patient Acceptable Symptom State (PASS) can be used.…”
mentioning
confidence: 99%
“…12,22,32 Additionally, many cohort studies suggest that hip arthroscopy for FAIS is associated with large and clinically relevant improvements in pain and function pre-to postoperatively. 17,23,24,30,39 Many patients, however, still present with persistent hip and groin pain and functional limitations after surgery, 17,18,21,39 indicating that discrepancies may exist between "getting better" and "feeling good." 25 To better understand if patients consider their current state of health (eg, pain and function) to be at an acceptable level after hip arthroscopy for FAIS, the Patient Acceptable Symptom State (PASS) can be used.…”
mentioning
confidence: 99%
“…Eight of 23 (35%) of the included studies described the use of a goniometer as the primary ROM measurement technique, with 5 of these studies specifying the use of a manual/handheld goniometer. Of those that used goniometric evaluation, 2 studies 27 , 28 reported dual-operator evaluation, 1 study 29 evaluated with a single operator, and the remaining 5 30 , 31 , 32 , 33 , 34 did not distinguish. In 1 additional study, 35 although not the primary purpose of the study, the authors did also report single-operator goniometric evaluation of ROM at 3-month clinical follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative changes in ER from each study's baseline were statistically significant in 20% (3/15), not statistically significant in 46.7% (7/15), and statistical significance was not reported in 33.3% (5/15). For those studies reporting statistically significant improvements in ER, effect size was weak in 33.3% (1/ 3) 27 of studies and large in 66.7% (2/3), 28,30 of studies. Pre-to postoperative measured changes in external rotation are presented in Figure 2C, whereas those studies evaluating a mix of unilateral and bilateral patients are presented in Figure 3C.…”
Section: External Rotationmentioning
confidence: 91%
See 1 more Smart Citation
“…Although HA is a well-established and effective treatment intervention for the management and alleviation of symptoms in athletes with diagnosed FAI, 24 to date the effect of surgical outcomes among patients with concomitant inguinal-related pathology is limited despite a high proportion of symptomatic FAI surgical cases citing groin pain as a major symptom. 8,20,30 Larson et al 19 reported on sports-related cases of athletic pubalgia and FAI and found 50% effectiveness of HA alone in terms of athletes returning to unrestricted sports, as compared with 25% effectiveness when surgical management of sports pubalgia was performed in isolation.…”
Section: Discussionmentioning
confidence: 99%